Palladium‐Catalyzed Oxidative Arylation of 1H‐Indazoles with Arenes. Issue 48 (13th November 2020) - Gambouz, Khadija; Abbouchi, Abdelmoula El; Nassiri, Sarah; Suzenet, Franck; Bousmina, Mostapha; Akssira, Mohamed; Guillaumet, Gérald; El Kazzouli, Saïd
Abstract : A simple method for the direct Pd(OAc)2 ‐catalyzed oxidative arylation of inactivated 1 H ‐indazole derivatives with simple arenes is reported. This method exhibits good reaction efficiency and good functional‐group tolerance. Using the developed method, 28 arylated products were prepared in yields up to 80 %. Abstract : Herein we report an efficient Pd(OAc)2 ‐catalyzed oxidative arylation of inactivated 1 H ‐indazole derivatives with simple arenes. The expected C3‐arylation products were obtained in moderate to good yields.